The Effect of Fermentation and Soaking Time on Water Content of Cocoa (Theobroma cacao L.) - Sri Wahyuni, Rahman; Abdul, Azis; Junaedi, Muhidong (Salaga Journal, 2024)
Post-harvest handling, particularly fermentation and soaking, significantly affects cocoa quality. This study investigates the effects of fermentation duration (3, 5, 7 days) and soaking time (1, 2, 3 hours) on the moisture content of MCC 02 cocoa beans. The fermented beans were sun-dried, and moisture content was analyzed using the wet/dry basis method. Results showed the lowest wet basis moisture content of 55.65% for beans fermented for 3 days and soaked for 1 hour, and the highest of 63.1% for beans fermented for 3 days and soaked for 2 hours. After drying, the control sample had a moisture content of 7.7% (63.5% before drying), while the lowest moisture content for beans fermented for 5 days with 1-hour soaking was 7.95%, and the highest was 10.65% for beans fermented for 3 days with 1-hour soaking, exceeding the SNI standard (6-7%). Temperature fluctuations (28 - 37°C) and weather-dependent drying prolonged the process, resulting in higher moisture content than the standard, indicating the need for controlled drying methods.